Feasibility of microalgal cultivation in a pilot-scale airlift-driven raceway reactor - Ketheesan, B.; Nirmalakhandan, N. (Elsevier, 2012)
A Scenedesmus sp. was cultivated in a 23-L airlift-driven raceway reactor under artificial lighting and laboratory conditions, in batch and continuous modes. In batch mode, a maximum volumetric biomass productivity of 0.085 dry g L 1 day 1 was achieved under sparging at a CO2-to-air ratio of 1%, and a maximum CO2 utilization efficiency of 33% was achieved at a CO2-to-air ratio of 0.25%. In continuous mode, the maximum volumetric biomass productivity was 0.19 dry g L 1 day 1. Biomass productivities per unit power input achieved in this reactor configuration (0.60–0.69 dry gW 1 day 1) were comparable to or better than those reported in the literature for different photobioreactor designs (0.10–0.51 dry gW 1 day 1). Based on the energy-efficient productivity and the high CO2 utilization efficiency demonstrated in this study, the proposed airlift-driven raceway design holds promise for cost-effective algal cultivation.
Keywords: Airlift-raceway reactor; Scenedesmus sp.; CO2 fixation; Productivity per unit volume